2012
DOI: 10.1002/pros.22612
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in CYP17 and CYP3A4 and prostate cancer in men of African descent

Abstract: BACKGROUND A meta and pooled analysis of published and unpublished case-control studies was peNorrformed to evaluate the association of CYP17 (rs743572) and CYP3A4 (rs2740574) polymorphisms and prostate cancer in men from the USA, Caribbean and Africa. METHODS Eight publications (7 studies) and two unpublished studies for CYP17 included 1,580 subjects (559 cases and 1,021 controls) and eleven publications and three unpublished studies for CYP3A4 included 3,400 subjects (1,429 cases and 1,971 controls). RES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…CYP17 is an enzyme involved in the androgen biosynthesis pathway and is the target pathway for abiraterone, a therapy for metastatic castration-resistant prostate cancer 64 . A meta-analysis of case-control studies found that CYP17 polymorphism increased the risk of prostate cancer development in African-American men only, with no effect on men from other races 65 .…”
Section: Gene Variation and Molecular Markersmentioning
confidence: 99%
“…CYP17 is an enzyme involved in the androgen biosynthesis pathway and is the target pathway for abiraterone, a therapy for metastatic castration-resistant prostate cancer 64 . A meta-analysis of case-control studies found that CYP17 polymorphism increased the risk of prostate cancer development in African-American men only, with no effect on men from other races 65 .…”
Section: Gene Variation and Molecular Markersmentioning
confidence: 99%
“…Meta-analyses have suggested that variants within CYP17A1 play a role in susceptibility to PCa among African-Americans but not in Caucasian or Asian populations (Ntais et al 2003;Wang et al 2011;Taioli et al 2013;Wang et al 2015). The reasons for the large ethnic differences might be explain by the observation that African-Americans experience earlier puberty, higher serum levels of total testosterone and a higher incidence of PCa (Loukola et al 2004).…”
Section: Cyp17a1 Rs743572 Gene Polymorphismmentioning
confidence: 99%
“…While the biomedical relevance of this work is extremely high (17% of American men will get prostate cancer), the genetics are proving to be somewhat more difficult than trait mapping in dogs. However, recent studies have successfully identified candidate loci associated with susceptibility to prostate cancer in high-risk families and certain populations (Jin et al 2012;Stott-Miller et al 2012;Taioli et al 2012;Xu et al 2013).…”
Section: Challenging Cancer Geneticsmentioning
confidence: 99%